Preferences in the Selection of German as a Cross-Interest Subject by 10th Grade Students of 2020 SMA Negeri 5 Malang - Rachmawati, Dessy Nour'Aini; Hidayat, Edy (Universitas Negeri Malang, 2024)
This research aims to describe the preferences and motivations behind the selection of German as a foreign language cross-interest subject of 10th-grade students of Cross-Interest German Class in the academic year 2020. This study used a qualitative descriptive method. The data collection technique was a questionnaire given through Google Forms and filled out directly by students. The sheet questionnaire is used to collect the result of the preferences and motivations behind the selection of German as a foreign language cross-interest subject. The collected data is grouped, submitted to the triangulator for checking, and conclusions are drawn to answer the problem formulation. The results showed that there are 7 preferences: self-understanding, self-knowledge, confidence in decisions, supporting facilities, the role of a third person, and consistency and recommendation. The motivations for selecting German are divided into 6: the desire to succeed, encouragement and need to learn, reward by learning, learning process, environmental circumstance, and availability of facilities.